Social Influence on Health IT Adoption Patterns of the Elderly: An Institutional Theory Based Use Behavior Approach - Bozan, Karoly; Davey, Bill; Parker, Kevin (Procedia computer science, 2015)
This study aims to investigate and improve understanding of the social forces that influence patient portal use behavior among the elderly. Underpinned by institutional theory and using the Unified Theory of Acceptance and Use of Technology, our proposed model examines the three social environmental factors of normative, mimetic, and coercive forces within the health Information Technology (HIT) context. The proposed model was tested using an empirical study of 117 subjects in the United States. Using the partial least squares method, the study found that coercive and mimetic pressures significantly influence patient portal use behavior. These findings signal that older people follow their providers’ advice and follow the behavior of a respected, higher-status peer from their network. Normative pressure was found to be an insignificant force, which indicated that older people do not follow the bandwagon effect.